Nutritional care in cancer patients in Italy: state of the art and perspectives - Valentina Da Prat; Valentina Caissutti; Lorenzo Perrone; Francesco Serra; Elisabetta Iannelli; Francesco De Lorenzo; Paolo Pedrazzoli; Riccardo Caccialanza (Nutrimentum et Curae)
Malnutrition is a common condition in cancer patients, with a detrimental impact on morbidity and mortality, as demonstrated by many clinical studies1,2. In particular, malnutrition is associated with prolonged hospitalization, higher rates of treatment-related toxicity, lower chemotherapy dose-intensity, reduced response to cancer treatment, impaired quality of life, and increased mortality.